ACCREDITATION OF LANGUAGE/LITERATURE/CULTURE CURRICULA AT THE FACULTY OF PHILOLOGY IN SERBIA - Markovic, Ljiljana; Francuski, Biljana; Markovic, Zoran (PEOPLE: International Journal of Social Sciences, 2017)
Although the Faculty of Philology – as one of 31 faculties at the University of Belgrade – is the oldest and the largest faculty of philology in Serbia (it was founded in 1908, and currently has some 350 teachers and 8,500 students), as well as one of the oldest and largest in the Balkans, its lengthy and successful tradition did not prevent the complete transformation of curricula in order to adapt them to the demands of the 21st century. The new, reformed programme of academic study has been implemented in line with the principles of the Bologna Declaration and contains elements of an integrated and transcultural approach to teaching foreign languages in higher education, together with the relevant literature and culture courses at bachelor, master and doctorate levels in over thirty departments of Belgrade Faculty of Philology. The purpose of this paper is to analyze the process of accreditation of the new programme and the outcomes of introducing the revised curricula at our academic institution, in order to highlight the success and benefits of the transformed academic courses, primarily for students but also for the staff.